2019
DOI: 10.1136/rapm-2019-100806
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Gender-Specific Authorship Disparities in the Pain Medicine Literature

Abstract: BackgroundGiven the readily increasing membership of the pain physician community, efforts toward correcting notable gender disparities are instrumental. The under-representation of women is particularly prevalent within leadership roles in academic medicine, thought to be driven largely by diminished research efforts. Consequently, we aimed to characterize gender differences among the highest impact pain literature.MethodsThe 20 highest cited articles per year from 2014 to 2018 were extracted from each of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…In recent years there has been a plethora of evidence confirming a lower representation of women in academic anesthesiology, pain medicine, critical care and clinical neuroscience, but with limited literature pertaining to women representation in neuroanesthesiology and neurocritical care academia 3–15. The findings of our study, which is an attempt to understand the representation of women first and corresponding authors in the academic subspecialty of neuroanesthesiology and neurocritical care, support those of a previous investigation that identified women first authors in 30.3% of neuroanesthesiology-related articles published in 2 leading anesthesiology journals with general content ( Anesthesiology and Anesthesia and Analgesia ) 4.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In recent years there has been a plethora of evidence confirming a lower representation of women in academic anesthesiology, pain medicine, critical care and clinical neuroscience, but with limited literature pertaining to women representation in neuroanesthesiology and neurocritical care academia 3–15. The findings of our study, which is an attempt to understand the representation of women first and corresponding authors in the academic subspecialty of neuroanesthesiology and neurocritical care, support those of a previous investigation that identified women first authors in 30.3% of neuroanesthesiology-related articles published in 2 leading anesthesiology journals with general content ( Anesthesiology and Anesthesia and Analgesia ) 4.…”
Section: Discussionsupporting
confidence: 87%
“…However, when compared with men, women continued to be relatively underrepresented in corresponding and last author roles. Interestingly, when compared with other medical specialties, Karri et al10 reported that women authors were not underrepresented in 7 impactful journals affiliated with the largest pain medicine societies when considering the national prevalence of pain medicine physicians. Although that study reported a trend toward an increased prevalence of first authorship by women over time (from 28.5% in 2014 to 35.5% in 2018), an in-depth analysis of the data revealed a nonsignificant trend towards lower representation of women authors within more impactful and higher cited literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, the authors noted the increase of female authorship in journals classified in the MeSH Journal Category "Pain" from 7.6% to 35.4% in 2002-2020 (236). Although this positive trend is certainly encouraging and heading towards parity, a recent study revealed a highly skewed gender disparity in the publications of the pain research community with a prevalence of 70.6% male first authors and 81.6% male senior authors (176). Their results, however, should be viewed with caution since:…”
Section: Journal Impact Factor (Jif) or Impact Factor (If)mentioning
confidence: 99%
“…(1) The first set includes bibliometric studies in which the IF appears as a "journal-level bibliometric index": generally, the authors provide tables in their Results section that include listings of journals containing "pain papers" in decreasing frequency order accompanied by the JIF of each journal (30, (176); and g. Kissin and Gelman assessed the publications on chronic postsurgical pain in leading journals (39), while Kissin assessed the long-term opioid treatment of chronic nonmalignant pain (43) and evaluated drugs for chronic pain (49).…”
Section: Journal Impact Factor (Jif) or Impact Factor (If)mentioning
confidence: 99%
“…The proportion of women practicing pain medicine has been increasing, but at a very slow rate: from 18.0% in 2013 to 18.3% in 2015 and 18.4% in 2017 (2022a). Women have also been found to be under-represented in impactful literature as identified by a study investigating the highest 20 cited articles from pain journals (Karri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%